Alternative therapies in the treatment of development dyslexia in preliterate children: an evaluation of retained reflex replication, vestibular system stimulation and related claims regarding early indicators - Smith, Elaine Claire (Trinity College (Dublin, Ireland). School of Psychology, 2007)
This study is concerned with the remediation, prediction and causal theories of developmental dyslexia and adopted a longitudinal, multi-factorial design in order to explore three principal claims. Exclusive methods of defining and diagnosing dyslexia, as well as dissatisfaction with narrow causal theories, have given (re)birth to alternative thinking about the disorder.
Keywords: Psychology, Ph.D.; Ph.D. Trinity College Dublin